Zadania ojca w świetle prawodawstwa pierwotnego Kościoła - Piasecki, Dariusz (Vox Patrum, 2024)
The article tries to show the role of the father in the light of the canons of the early Church, starting from the beginnings of Christianity until the year 600. It concerns issues such as the father's responsibility for the faith and salvation of children, proper upbringing of offspring, protection of children against various forms of violence, and providing the child with appropriate financial resources. (maintaining) and maintaining the father's authority in the context of responsibility for one's word.